Long-Acting Efavirenz and HIV-1 Fusion Inhibitor Peptide Co-loaded Polymer-Lipid Hybrid Nanoparticles: Statistical Optimization, Cellular Uptake, and In Vivo Biodistribution - Surve, Dhanashree H; Jirwankar, Yugandhara B; Dighe, Vikas D; Jindal, Anil B (Molecular pharmaceutics, 2020)
The objective of the present study was to develop long-acting efavirenz (Efa)-enfuvirtide (Enf) Co-loaded polymer-lipid hybrid nanoparticles (PLN) with improved intracellular delivery to target T-cells and macrophage cells located in multiple human immunodeficiency virus sanctuaries. The Box-Behnken design was utilized to optimize three high-risk factors, namely, Efa amount, sonication time for primary emulsion, and sonication time for aqueous nanodispersion obtained from preliminary studies. Lyophilized Efa-Enf Co-loaded PLN using trehalose elicited spherical morphology, drug amorphization on incorporation, and absence of drug-excipient interaction. In vitro release studies revealed an sustained release of both the drugs from PLN with the differential release profile. Efa-Enf Co-loaded PLN exhibited low hemolytic, platelet and leukocyte aggregation as well as low cytotoxicity in Jurkat E6.1 T-cells and U937 macrophage cells. Circular dichroism spectra confirmed the presence of an α-helix form of Enf after encapsulation in PLN. Coumarin-6-loaded PLN exhibited enhanced cellular uptake in Jurkat E6.1 T-cells and U937 macrophage cells in comparison to free coumarin-6, as evidenced by fluorescence microscopy and flow cytometry. In vivo biodistribution studies after intravenous administration of near-infrared dye-loaded PLN (surrogate for Efa-Enf PLN) revealed non-uniform distribution within 2 h in the order of spleen ≥ liver > lymph node > thymus > lungs > female reproductive tract (FRT) > heart > kidneys > brain. However, subcutaneous administration caused non-uniform biodistribution after 3 days, eliciting a long-acting slow release from the injection site depot until day 5 in the infection-spread site (lymph nodes and FRT), reservoir sites (liver and spleen) and the difficult-to-access site (brain). Furthermore, it presents a vital illustration of the available tissue-specific drug concentration prediction from simulated surrogate PLN.The objective of the present study was to develop long-acting efavirenz (Efa)-enfuvirtide (Enf) Co-loaded polymer-lipid hybrid nanoparticles (PLN) with improved intracellular delivery to target T-cells and macrophage cells located in multiple human immunodeficiency virus sanctuaries. The Box-Behnken design was utilized to optimize three high-risk factors, namely, Efa amount, sonication time for primary emulsion, and sonication time for aqueous nanodispersion obtained from preliminary studies. Lyophilized Efa-Enf Co-loaded PLN using trehalose elicited spherical morphology, drug amorphization on incorporation, and absence of drug-excipient interaction. In vitro release studies revealed an sustained release of both the drugs from PLN with the differential release profile. Efa-Enf Co-loaded PLN exhibited low hemolytic, platelet and leukocyte aggregation as well as low cytotoxicity in Jurkat E6.1 T-cells and U937 macrophage cells. Circular dichroism spectra confirmed the presence of an α-helix form of Enf after encapsulation in PLN. Coumarin-6-loaded PLN exhibited enhanced cellular uptake in Jurkat E6.1 T-cells and U937 macrophage cells in comparison to free coumarin-6, as evidenced by fluorescence microscopy and flow cytometry. In vivo biodistribution studies after intravenous administration of near-infrared dye-loaded PLN (surrogate for Efa-Enf PLN) revealed non-uniform distribution within 2 h in the order of spleen ≥ liver > lymph node > thymus > lungs > female reproductive tract (FRT) > heart > kidneys > brain. However, subcutaneous administration caused non-uniform biodistribution after 3 days, eliciting a long-acting slow release from the injection site depot until day 5 in the infection-spread site (lymph nodes and FRT), reservoir sites (liver and spleen) and the difficult-to-access site (brain). Furthermore, it presents a vital illustration of the available tissue-specific drug concentration prediction from simulated surrogate PLN.